Moderate-to-severe ARDS: COVID-19 patients compared to influenza patients for ventilator parameters and mortality. Issue 2 (11th April 2023) - Maamar, Adel; Guillot, Pauline; Joussellin, Vincent; Delamaire, Flora; Painvin, Benoit; Bichon, Anaëlle; de la Jartre, Océane Bernard; Mauget, Matteo; Lesouhaitier, Mathieu; Tadié, Jean Marc; Terzi, Nicolas; Gacouin, Arnaud
Background: This study aimed to compare ventilatory parameters recorded in the first days of acute respiratory distress syndrome (ARDS) and mortality at day 60 between coronavirus disease 2019 (COVID-19) and influenza ARDS patients with arterial oxygen tension ( P aO2 )/inspiratory oxygen fraction ( F IO2 ) ≤150 mmHg. Methods: We compared 244 COVID-19 ARDS patients with 106 influenza ARDS patients. Driving pressure, respiratory system compliance ( C rs ), ventilator ratio, corrected minute ventilation ( V ′Ecorr ) and surrogate of mechanical power (index=(4×driving pressure)+respiratory rate) were calculated from day 1 to day 5 of ARDS. A propensity score analysis and a principal component analysis (PCA) were performed. Results: On day 1 of ARDS, COVID-19 patients had significantly higher P aO2 / F IO2 (median (interquartile range) 97 (79–129.2) versus 83 (62.2–114) mmHg; p=0.001), and lower driving pressure (13.0 (11.0–16.0) versus 14.0 (12.0–16.7) cmH2 O; p=0.01), ventilatory ratio (2.08 (1.73–2.49 versus 2.52 (1.97–3.03); p<0.001), V ′Ecorr (12.7 (10.2–14.9) versus 14.9 (11.6–18.6) L·min −1 ; p<0.001) and index (80 (70–89) versus 84 (75–94); p=0.004). PCA demonstrated an important overlap of ventilatory parameters recorded on day 1 between the two groups. From day 1 to day 5, repeated values of P aO2 / F IO2, arterial carbon dioxide tension, ventilatory ratio and V ′Ecorr differed significantly between influenza and COVID-19 patients in the unmatched and matched populations. Mortality at day 60 did not differ significantly after matching (29% versus 21.7%; p=0.43). Conclusions: Ventilation was more impaired in influenza than in COVID-19 ARDS patients on the first day of ARDS with an important overlap of values. However, mortality at day 60 did not differ significantly in the matched population. In COVID-19 and influenza patients with mild-to-moderate ARDS managed similarly for mechanical ventilation, dead space estimates were higher in COVID-19 patients than in influenza patients in the first days of ARDS but short-term mortality was similar https://bit.ly/3ZYeXWG